2011
DOI: 10.1177/0748233711399321
|View full text |Cite
|
Sign up to set email alerts
|

Paraphenylene diamine hair dye poisoning in an adolescent

Abstract: A 14-year-old female was referred to the pediatric nephrology unit with a short history of progressive angio-oedema of the face requiring tracheostomy. She ingested an unusual substance which caused swollen tongue, cervical oedema and dark coloured brown urine. These clinical features with the laboratory tests confirmed the diagnosis of paraphenylene diamine (PPD) poisoning. Psychological assessment confirmed that the child had severe depression. The suicide attempt was just immediately after failure in the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…Accidental or intentional poisoning results in systemic toxicity [11] in a dose-dependent manner [12]. In our study, we observed the classical features of poisoning within four to six hours of ingestion.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Accidental or intentional poisoning results in systemic toxicity [11] in a dose-dependent manner [12]. In our study, we observed the classical features of poisoning within four to six hours of ingestion.…”
Section: Discussionsupporting
confidence: 56%
“…During the hospital stay, 24 (48%) required ventilatory support for airway compromise; among them, two (4%) patients died due to respiratory failure during hospital stay. The mean ICU stay was 6.35 ± 4.19 days (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). The duration of ventilator support was 6.19 ± 4.19 days (1-13).…”
Section: Resultsmentioning
confidence: 99%
“…Apart from intentional or accidental excessive exposure to PPD which results in above manifestations, the routine use of this compound on the regular basis for a long time can also lead to toxic effects. [10] Membranous nephropathy has also been reported when toxicity occurs in smaller doses. It occurs due to formation of immune complexes.…”
Section: Discussionmentioning
confidence: 99%
“…p-Phenylenediamine * (78) m-Aminophenol (76) Toluene-2,5-diamine (sulfate) (80) m-Aminophenol * (75) p-Phenylenediamine (50) m-Aminophenol (68) p-Aminophenol * (60) Toluene-2,5-diamine (sulfate) (49) 2-Methylresorcinol (39) N,N-Bis(2-hydroxyethyl)-pphenylenediamine * (41) 4-Amino-2-hydroxytoluene (35) 4-Amino-2-hydroxytoluene (35) 2,4-Diaminophenoxyethanol * (36) 2-Methylresorcinol (33) p-Aminophenol (25) 4-Amino-2-hydroxytoluene * (36) p-Aminophenol (32) 2,4-Diaminophenoxyethanol-HCl (25) 2-Methylresorcinol (32) 2,4-Diaminophenoxyethanol-HCl (30) 4-Amino-m-cresol (18) Toluene-2,5-diamine *(21) N,N-Bis(2-hydroxyethyl)-p-phenylenediamine sulfate Designates allergens that were reported as either a free base, sulfate, or HCL.…”
mentioning
confidence: 99%